STRATEGI PENINGKATAN OMZET PENJUALAN PADA UMKM KOTA MADIUN MENGGUNAKAN PENERAPAN YOUTUBE SEBAGAI MEDIA DALAM KOMUNIKASI MASSA - Hedi Pandowo; Hamim Tohari; Dian Kusumaningrum; Nova Maulud Widodo; Sugiharto (Politeknik Negeri Sriwijaya, 2023)
Mass communication is defined as all forms of communication that convey information openly through technical dissemination media indirectly and use one-way communication methods aimed at the public. Communicants in mass communication are also anonymous and heterogeneous. With today's technological developments, old media such as books, magazines, newspapers and radio do not mean they will be abandoned and forgotten and replaced with new media. Rather, the old media is processed and adapted into new media by applying digitization technology. The emergence of new media today has made the name Youtube a major concern in the eyes of the public. Even since the presence of Youtube as a new media, not a few television users and viewers have turned to Youtube. This new media is more easily accessible and accessible to the public. I support the media for introducing products to the public. With the recognition of products by the public through YouTube media, it will increase public interest in the product and will further increase sales turnover